Implementation of Accountability and Reporting Based on Islamic Sharia in Efforts to Prevent Regional Government Financial Fraud - Abdul Muftih; Ssonku Muhammedi (IAIN Syekh Nurjati Cirebon, 2024)
The main objective of this study is to prevent fraud in the local government sector on the island of Java by increasing government accountability using the cultivation of the values of the teachings of the kindness of Javanese ancestors, including; Indra Brata (Sky), Yama Brata (Star), Surya Brata (Sun), Candra Brata (Moon), Bayu Brata (Wind), Kuwera Brata (Earth), Baruna Brata (Ocean), Agni Brata (Fire) in each regional apparatus. The concept of this research used attribution theory, which provides an explanation of the reasons why someone does something or chooses to act in a certain way, so that good accountability based asthabrata greatly supports fraud prevention in the local government sector.This research collects data using the literature study method from sources with the theme of fraud and corruption, such as journals and a financial audit agency report on the island of Java between 2020 and 2024. The results of this study indicate that as a whole the implementation of asthabrata values is not optimal in increasing accountability in order to prevent financial fraud on the island of Java. As an implication, Javanese philosophy of